Ploidy dimorphism and reproductive biology in Stenodrepanum bergii (Leguminosae), a rare South American endemism - Caponio, I. (2011)
This is the first report on chromosome numbers and the reproductive behaviour in Stenodrepanum Harms, a rare endemic and monotypic legume genus from the arid and salty areas of central–western Argentina. Sixty individuals belonging to two populations from two salty areas (“salinas”) were surveyed and included mostly triploid (2n = 3x = 36) and only two diploid (2n = 2x = 24) plants. Meiosis in diploids is regular, with bivalent pairing and uniform and viable pollen. In contrast, meiosis in triploids is characterized by high trivalent pairing, with irregularly shaped pollen and variation in cytoplasm content and stainability, which is in agreement with an unbalanced segregation occurring in anaphases I and II. However, different triploid plants/individuals showed various degrees of pollen fertility, which may be attributed to particular genotypes. Research on reproductive biology events indicates sexual cross-pollinated reproduction enhanced by protogyny in both cytotypes. All plants produced seeds, but seedlings were only recovered from diploid plants pollinated with triploids, and even those eventually perished. Chromosome counts in these seedlings revealed aneuploid chromosome numbers owing to the combination of unbalanced gametes.